"Trying to Find the Middle Ground": Drug Policy and Harm Reduction in Black Communities. (January 2014) - Eversman, Michael H.
U.S. federal drug policy has long emphasized criminalization and incarceration, and many negative policy outcomes have disproportionately impacted communities of color and Blacks in particular. The framework of harm reduction informs a range of alternative policy strategies from decriminalization to legalization, treating drugs more as a public health than a criminal justice issue. While Black communities are seen as opposing harm reduction with illicit drugs, Black leadership has recently supported ending the war on drugs. Using in-depth interviews with 21 substance abuse service providers in a Northeastern U.S. urban hub, this study explores views toward the potential impact of, and support for, harm reduction illicit drug policies in Black U.S. communities. Cognizant of the racially skewed impact of drug policies, respondents endorsed policy changes but were generally mixed on harm reduction, opposing liberalization of "hard" drugs, yet supporting it for marijuana given its link to race-based policing. Respondents indicate many Black communities need more than drug policy change, at best seeing harm reduction as only part of larger scale reinvestment. Findings inform considerations of reforming drug policy strategies and priorities for these communities, given views toward illicit drugs and racially skewed outcomes of current drug policy.